A simulation of particle movement by using DEM-DPM - Aziz N.A.; Zawawi M.H.; Mazlan A.; Ramli M.Z.; Radzi M.R.M.; Abas A.; Azman A. (American Institute of Physics Inc., 2023)
Shoreline changes that leads to coastal erosion is a natural phenomenon that concern many researchers worldwide. It is important to understand the particle movement of the sand that induced by sea waves to predict the changes of the shorelines. In the present study, sand sediment erosion model has been developed to determine which division that has high movement of the particle by using DEM-DPM method. The simulation works reported that, the velocity magnitude of the particle at the upper part is high while at the lower part is low. It is also found that, the total pressure at the upper part of the sand sediment is low compare to the lower part of the sediment. Furthermore, the most critical division can be determined through this simulation as the critical division has a high movement of the particle. Based on the findings, the most critical division for this sand sediment model is Division A as the particle on that division has a high movement of the particle due to high velocity magnitude and low total pressure. 2020 Author(s).